Migration strategy of cloud collaborative computing for delay-sensitive industrial IoT applications in the context of intelligent manufacturing - Wang, Ke (Computer communications, 2020)
In the context of intelligent manufacturing, machinery and equipment in the industrial manufacturing process form the “industrial Internet of Things.” In this process of interlocking production, the requirements for sensor data delay typically reach the millisecond level. Once the data is delayed, the equipment will be shut down, which will make the production difficult or dangerous. In the context of intelligent manufacturing, local computers have been unable to complete calculations and decisions quickly and on time for the huge computing demands. Therefore, the cloud computing migration mode needs to be introduced, but cloud computing migration will cause additional delays. Based on the above problems, this paper designs a cloud cooperative migration strategy based on the information exchange structure of the industrial Internet of Things and the delay mechanism caused by the migration. The feasibility of selecting the optimal migration strategy based on task partitioning is verified by simulation.